Evaluasi Sifat-Sifat Fisik dan Kimiawi Beberapa Jenis Jagung Produksi Sukamandi dan Garut - Rob Mudjisihono; Koswara Koswara; Muhadji D. Moentono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1989)
Physical and chemical evaluation of fifteen varieties of corn produced in Sukamandi and Garut. Micrometer was used to measure kernel size and shape (dimension). Physical analysis showed that corn planted at high elevation (Garut,. 700 in a.s.1) produce larger kernels, i.e. 9.7 mm length and 9.0 mm width, than those produced at lower elevation (Sukamandi, 12 m a.s.l) which their dimensions were only 8.7 mm length and 8.6 mm width. The RRS corn width had the largest kernel dimensions i.e. 9.5 mm length and 9.1 mm wide. The amylose and protein contents were 19.2-21.3% and 9.0- 10.33%, respectively.